Avaliação da necrose óssea produzida por diferentes protocolos de aplicação de nitrogênio líquido em diáfise femural de ratos - Costa, Fabio Wildson Gurgel (2008)
The maxillo-mandibular facial complex may be affected by a variety of injuries that, although benign, present themselves locally aggressive. Treatment of these conditions have raised doubts as to choose the best therapy to be established, since the conservative treatment has been associated with high rates of recurrence, while the radical, but usually lead to a definitive cure, has created severe aesthetic - functional. In this context, adjuvant therapies, such as cryosurgery with liquid nitrogen, have been combined with conservative modalities with the aim of reducing the rate of recurrence without increasing its morbidity. The purpose of this study was to evaluate the effects induced by the application of liquid nitrogen in femoral diaphysis of rats. Were performed in femoral diaphysis of 42 rats, three local applications and sequential liquid nitrogen, interspersed with periods of 5 minutes, time of exposure that ranged from 1 or 2 minutes. After 1, 2, 4 and 12 weeks, the animals were sacrificed and the specimens were collected and processed and analyzed histomorphological and histomorphometrically. Histologically, the second week trial was a maximum of bone necrosis in both protocols. The depth and extent of bone necrosis average maximum induced by the Protocol of 1 minute was, respectively, 124,509 and ìm 2087.094 ìm, while that of 2 minutes were, respectively, 436424μm and 12046.426 micrometers. Based on the findings of this study, we can conclude that the protocol of 2 minutes produced a bone necrosis more pronounced than that of 1 minute, and therefore more suitable for the treatment of aggressive bone lesions covering the jaw.